Applicability of evidence from previous systematic reviews on immunotherapy in current practice of childhood asthma treatment: a GRADE (Grading of Recommendations Assessment, Development and Evaluation) systematic review. Issue 12 (28th December 2017) - van de Griendt, Erik-Jonas; Tuut, Mariska K; de Groot, Hans; Brand, Paul L P
Abstract : Objective: Because most children with asthma now use inhaled corticosteroids (ICS), the added benefit of immunotherapy in asthmatic children needs to be examined. We re-assessed the effectiveness of subcutaneous (SCIT) and sublingual immunotherapy (SLIT) in childhood asthma treatment focusing on studies with patient-relevant outcome measures and children using ICS. Methods: We used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach to systematically search and appraise the evidence using predefined critical patient-relevant outcomes (asthma symptoms, asthma control and exacerbations). We searched to retrieve systematic reviews and randomised controlled trials on immunotherapy for asthma in children (1960–2017). We assessed the quality of the body of evidence with GRADE criteria. Results: The quality of the evidence for SCIT was very low due to a large risk of bias and indirectness (dated studies in children not using ICS). No effect of SCIT was found for asthma symptoms; no studies reported on asthma control. For asthma exacerbations, studies favoured SCIT. We have little confidence in this effect estimate, due to the very low quality of evidence. For SLIT, quality of the evidence was very low due to a large risk of bias, indirectness and imprecision. The outcome 'asthma symptoms' could not be calculated due to lack of standardisation and large clinical heterogeneity. Other predefined outcomes were not reported. Conclusion: The beneficial effects of immunotherapy in childhood asthma found in earlier reviews are no longer considered applicable, because of indirectness (studies performed in children not being treated according to current asthma guidelines with ICS). There was absence of evidence to properly determine the effectiveness or lack thereof of immunotherapy in asthma treatment in children with ICS.